Praktik Pembagian Harta Waris Terhadap Kerukunan Keluarga Menurut Tokoh Masyarakat Studi Kasus di Desa Campur Kecamatan Gondang Kabupaten Nganjuk - Umami, Hafidhul; Sholichah , Umi Chamidatus (USRATUNA: Jurnal Hukum Keluarga Islam, 2025)
This study examines the practice of inheritance distribution and its impact on family harmony from the perspective of community leaders in Campur Village, Gondang District, Nganjuk Regency. Normatively, Islamic inheritance law (farāʾiḍ) regulates the distribution of inheritance in detail based on the Qur’an and Hadith. However, in social practice, the people of Campur Village tend not to apply the farāʾiḍ system in a pure form, instead adopting customary and family-based distribution with an equal-sharing principle. This research employs a descriptive qualitative approach with a field research method, utilizing interviews and observations involving local community leaders. The findings indicate that the main reason for the non-implementation of Islamic inheritance law is the community’s perception that farāʾiḍ-based distribution is considered unfair and has the potential to trigger family conflict. Community leaders believe that customary distribution is more effective in maintaining harmony, peace, and family unity. From the perspective of Islamic law, such practices cannot be fully classified as valid ‘urf, yet they may be justified provided that all heirs are aware of their respective legal shares and mutually agree to a peaceful settlement, as stipulated in Article 183 of the Compilation of Islamic Law. This study highlights the importance of the role of religious and community leaders in providing a comprehensive understanding of justice in Islamic inheritance law in order to bridge the gap between normative legal justice and social perceptions of justice within society.